Pemberdayaan Kelompok Tenun Nari-Nari Melalui Pewarnaan Benang Menggunakan Ekstrak Kayu Kuning Dan Kayu Mahoni - R, Ruslan; Wiraningtyas, Agrippina; Sandi, Ahmad; Nasir, Muhammad (Jurnal Pemberdayaan Masyarakat, 2020)
The "Nari-Nari" Weaving Village in Rabadompu Timur Village, Bima City, is a community group engaged in the weaving industry which has been carried on for generations. During this time, Bima woven fabric products use yarn raw material that has been colored using synthetic dyes. Yarn with synthetic dyes has a more diverse color, the fabric coloring process is easier and the cost is cheap, but synthetic dyes are carcinogenic and harmful to the environment. The solution to the problems faced by using natural dyes obtained from plants. This activity aims to train the Nari-Nari weaving group in yarn coloring using natural dyes. The method used is training through several stages of the activity namely the stage of socialization of activities; the training stage of yarn dyeing and woven fabric production. The dyes used are yellow wood extract and mahogany wood. The results obtained in this activity are the colored yarn has a different color based on the extract of the dye and fixation material. In yellow wood obtained with a maroon red color on alum, black on tunjung and reddish beige on lime. In mahogany wood is obtained beige on alum, black gray on tunjung and beige on lime.